Noise exposure amongst Kuantan municipal council workers (MPK) - Ali Hanifiah, Nurlin; Mohd Zain, Siti Rashidah; Dzulkarnain, Ahmad Aidil Arafat; Jamaluddin, Saiful Adli (2012)
Occupational hearing loss continues to be among the 10 leading occupational diseases among industrial workers. Hearing loss is sensorineural hearing deficit that begins at higher frequencies (3 kHz to 6 kHz) and develop gradually as a results of excessive exposure of noise. A cross sectional study of hearing status among employees in Kuantan Municipal Council (MPK), Malaysia was conducted in August 2010 until mid of January 2011. Seventy-seven subjects consist of eleven females and sixty-six males aged between 20 to 58 year-old (mean; 39.45 ± 8.63) were involved in this study. Subjects were recruited from 5 different Units which are Landscape, Mechanical, Vector, Special Action Unit and Maintenance Unit. The aim of this study is to measure the hearing level and noise dose amongst Kuantan Municipal Council workers who work under noise exposure. Hearing statuses were accessed by using tympanometry and pure tone audiometery tests. Other factors that might be associated to hearing loss were also determined in this study. Results showed that 52 subjects (67.5 %) had normal hearing and 25 subjects (32.5 %) had hearing loss. Noise exposure measurement showed that the noise level in the workplace reached the action level of 85 dBA and exceeded the permissible exposure level of 90 dBA. Pearson Correlation Coefficient revealed that there was no significant relationship between service length and hearing level at 3, 4 and 6 kHz. Thus, this study revealed that MPK workers are at substantial risk of developing hearing loss due to the noise exposure. Urgent action should be taken by the MPK’s administration to ensure individual noise exposures are within permissible limits.